EFEKTIVITAS TERAPI MINDFULNESS DALAM MENINGKATKAN KUALITAS TIDUR IBU NIFAS DI KLINIK SRIKANDI HUSADA - Rada Elya Arsya; Dwi Astuti; Irawati Indrianingrum (Yayasan Nusantara Hasana Berdikari, 2026)
Sleep quality is one of the common problems experienced by postpartum mothers due to physical, hormonal, and psychological changes, as well as adaptation to the new role as a mother. Sleep disturbances during the postpartum period can affect maternal health and the quality of infant care. One of the non-pharmacological interventions that can be used to improve sleep quality is mindfulness therapy. This study aimed to determine the effect of mindfulness therapy on the sleep quality of postpartum mothers. The study used a pre-experimental design with a one-group pretest–posttest approach. The research subjects were postpartum mothers who met the inclusion criteria. The intervention in the form of mindfulness therapy was administered in three sessions over one week according to standard operating procedures. Sleep quality was measured using the pittsburgh sleep quality index (psqi) questionnaire. The pre-test measurement was conducted before the mindfulness intervention, while the post-test measurement was carried out after all intervention sessions had been completed. The results showed that the average psqi score before the intervention was 12.3, indicating poor sleep quality among postpartum mothers. After mindfulness therapy was administered, the average psqi score decreased to 6.4, indicating an improvement in the respondents’ sleep quality. Statistical analysis was conducted to compare psqi scores before and after the intervention. The wilcoxon test results showed a significant difference between pre-test and post-test psqi scores with a p-value < 0.05, indicating that mindfulness therapy had a significant effect on improving postpartum mothers’ sleep quality. Based on these findings, it can be concluded that mindfulness therapy is effective as a non-pharmacological intervention in improving the sleep quality of postpartum mothers and may be considered for implementation in postpartum maternal healthcare services.